The Perceptions of Educators Relating to the Promotion of the Psychological Well-Being of Abandoned Children - Attar, Fatima; Ouadi, Khadija (Journal of Advanced Research in Social Sciences, 2021)
Promoting the psychological well-being of abandoned children raises specific issues. These children have no choices but to live in residential child care institutions. They are called to take part in society, to become autonomous and competent adults. However, these children present difficulties that result in impairment of self-esteem and are identified by negative feelings, as well as failures in their relationship with others. Researchers point out that the satisfaction of the three basic psychological needs: the need for autonomy, the need for social affiliation and the need for competence, is essential to the growth of the individual’s integrity and well-being. Our ultimate interest is to contribute through this work, to the development of educational practices and the quality of care in the child care institutions. From this perspective, this qualitative research aims to explore the educators’ perceptions of psychological well-being of abandoned children, actions they take and the contributions of professional services to promote it. Semi-structured individual interviews were conducted with educators (N=10) in a residential child care institution. The results show that the educator’s perceptions of psychological well-being go in the same direction as the definitions of psychological well-being in the scientific literature. The majority of their actions tend towards satisfaction of the three fundamental psychological needs, which are essential to the development of psychological well-being. They also underlined the important role of professional services, material and human resources in this direction. This research allowed identifying five specific ways to promote the psychological well-being of abandoned children in the residential child care institutions.